I Caffè pedagogici in italia - Fabio Olivieri (Firenze University Press, 2018)
ùThis paper offers a critical analysis of the experiences shared within a community of practitioners called Pedagogical Café. This is an informal network of pedagogues and educators who deal with educational themes through a methodology of comparison, exchange, and mutual enrichment. The purpose of meetings is to support and improve the skills of reflexive thinking and professional  awareness of educational practitioners.